2015
DOI: 10.1371/journal.pone.0138067
|View full text |Cite
|
Sign up to set email alerts
|

Serum Urate and Incident Cardiovascular Disease: The Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: ObjectiveThere is controversy about whether serum urate (sUA) predicts future cardiovascular disease (CVD) independently of classical risk factors, and the age at which any prediction starts. We studied the sUA-CVD association among generally healthy adults.MethodsCARDIA recruited 5115 black and white individuals aged 18–30 years in 1985–1986 (year-0). Fatal and nonfatal CVD events by year 27 (n = 164) were ascertained during annual contacts and classified using medical records. The association with sUA (year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
3
9
0
2
Order By: Relevance
“…The recent study concerning on the relationship between HUA and CAD in patients ≤35 years of age (the 2015 CARDIA study) showed that after adjusting for demographic and lifestyle factors, the baseline SUA concentration was positively associated with the prevalence of CVD (HR, 1.21; 95% CI, 1.05–1.39; p  = 0.005). This positive association was not significant in the full model due to the simultaneous effects of traditional risk factors (HR, 1.09; 95% CI, 0.94–1.27; p  = 0.24) [14]. This conclusion was similar to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The recent study concerning on the relationship between HUA and CAD in patients ≤35 years of age (the 2015 CARDIA study) showed that after adjusting for demographic and lifestyle factors, the baseline SUA concentration was positively associated with the prevalence of CVD (HR, 1.21; 95% CI, 1.05–1.39; p  = 0.005). This positive association was not significant in the full model due to the simultaneous effects of traditional risk factors (HR, 1.09; 95% CI, 0.94–1.27; p  = 0.24) [14]. This conclusion was similar to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Several prospective studies consistently demonstrated the positive relationship between SUA level and risk of cardiovascular diseases in general populations815. However, the association was inconsistent in patients with diabetes323334.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, high uric acid levels and low bilirubin concentrations were observed to be associated with CVD89. Uric acid is a metabolic end product of purine metabolism in humans and possesses pro-oxidant and antioxidant dual properties.…”
mentioning
confidence: 99%
“…These findings were robust after adjusting for multiple traditional risk factors for hypoglycaemia. Previous epidemiological or experimental studies reported that SUA was positively correlated with disorders of lipid metabolism, hemodynamic abnormalities [25], cardiovascular disease [26], pre-diabetes (i.e. impaired fasting glucose, mildly elevated HbA 1c , hyperinsulinemia and insulin resistance) [9,27] and diabetes [4,19].…”
Section: Discussionmentioning
confidence: 99%